Matrix Metalloproteinase‐2 Activity is Associated with Divergent Regulation of Calponin‐1 in Conductance and Resistance Arteries in Hypertension‐induced Early Vascular Dysfunction and Remodelling - Parente, Juliana M.; Pereira, Camila A.; Oliveira‐Paula, Gustavo H.; Tanus‐Santos, José E.; Tostes, Rita C.; Castro, Michele M. (Basic & clinical pharmacology & toxicology, 2017)
Matrix metalloproteinase (MMP)‐2 participates in hypertension‐induced maladaptive vascular remodelling by degrading extra‐ and intracellular proteins. The consequent extracellular matrix rearrangement and phenotype switch of vascular smooth muscle cells (VSMCs) lead to increased cellular migration and proliferation. As calponin‐1 degradation by MMP‐2 may lead to VSMC proliferation during hypertension, the hypothesis of this study is that increased MMP‐2 activity contributes to early hypertension‐induced maladaptive remodelling in conductance and resistance arteries via regulation of calponin‐1. The main objective was to analyse whether MMP‐2 exerts similar effects on the structure and function of the resistance and conductance arteries during early hypertension. Two‐kidney, one‐clip (2K‐1C) hypertensive male rats and corresponding controls were treated with doxycycline (30 mg/kg/day) or water until reaching one week of hypertension. Systolic blood pressure was increased in 2K‐1C rats, and doxycycline did not reduce it. Aortas and mesenteric arteries were analysed. MMP‐2 activity and expression were increased in both arteries, and doxycycline reduced it. Significant hypertrophic remodelling and VSMC proliferation were observed in aortas but not in mesenteric arteries of 2K‐1C rats. The contractility of mesenteric arteries to phenylephrine was increased in 2K‐1C rats, and doxycycline prevented this alteration. The potency of phenylephrine to contract aortas of 2K‐1C rats was increased, and doxycycline decreased it. Whereas calponin‐1 expression was increased in 2K‐1C mesenteric arteries, calponin‐1 was reduced in aortas. Doxycycline treatment reverted changes in calponin‐1 expression. MMP‐2 contributes to hypertrophic remodelling in aortas by decreasing calponin‐1 levels, which may result in VSMC proliferation. On the other hand, MMP‐2‐dependent increased calponin‐1 in mesenteric arteries may contribute to vascular hypercontractility in 2K‐1C rats. Divergent regulation of calponin‐1 by MMP‐2 may be an important mechanism that leads to maladaptive vascular effects in hypertension.